Development Of Panel Sandwich Products Made From Bamboo - Naresworo Nugroho; Jajang Suryana; . Febriyani; Hady Ikhsan (Department of Agroindustrial Technology, Bogor Agricultural University, 2009)
Composite panel products such as sandwich panel can be used in building construction. The purpose of the first research is to find out the physical and mechanical properties of sandwich panel made from three bamboo species.The species of bamboo used were tali (Gigantochloa apus), ampel (Bambusa vulgaris) and hitam (Gigantochloa atroviolaceae). Those bamboo were used as core, whereas plywood was used as face and back. Part of core represented by pieces of bamboo which was cutting along 4 cm with three compilation patterns of bamboo, those were full circular bamboo pattern, bamboo cleave pattern and the mixed of them. Materials that used in second research were tali bamboo used as core with thickness of 3 cm, 4 cm, and 5 cm and three synthetic adhesives (epoxy, polyurethane, isocyanate). The physical and mechanical properties tested of sandwich panel were moisture meter, density, modulus of elasticity (MOE), modulus of rupture (MOR) and internal bond strength. The testing results of the panel were compared to JIS A 5908-2003 standard. The result of physical properties testing from the first research indicated that all of the density of sandwich panel met in the range required by JIS A 5908 standard. The result of mechanical properties showed that sandwich panel made from full circular bamboo pattern raced the best MOE and MOR value. Mean while the species of bamboo did not affect significantly to the mechanical properties of the sandwich panel. Result of second research showed that moisture content and density of sandwich panel has fulfilled the standard limit of JIS A 5890-2003. In mechanical characteristic testing for MOE value passed the standard limit, but MOR value of panel does not fulfill the standard of JIS A 5890-2003. It is expected by off-bonding of adhesive between bamboo and plywood. It can be concluded that combination of sandwich panel with core 3 cm and epoxy resin had the best of physical and mechanical properties.Keywords: bamboo sandwich panel, adhesives, physical properties, mechanical properties.